PETROPHYSICAL ROCK TYPE-BASED RESERVOIR CHARACTERIZATION OF EARLY MIOCENE CARBONATE RESERVOIRS OF BATURAJA FORMATION, RAMA FIELD, SUNDA BASIN - Wibowo, Suryadi
Rama Field is located in the southern part of Sunda Basin. Its main reservoir, the Upper Baturaja Unit carbonate contains most of the oil resources in Rama Field, yet, only 12% of these have been produced to date. Future water injection and redevelopment plans of this field, as the consequence, require detail analysis through static and dynamic approaches. This thesis focuses on the petrophysical rock type–based static reservoir characterization through the identification of rock type, its composition and distribution. Hence, the main goal to obtain a comprehensive understanding of the petrophysical properties of the reservoir can be achieved. Core data with a total length of 410 ft from four wells, 305 core plugs, each of them is measured for its porosity and permeability and sampled for thin section analysis, combined with 108 well data are used in this study. Facies, facies association and diagenetic history analyses are performed to understand the influence of facies, depositional environments and diagenesis to the development of petrophysical rock types (PRT). Petrographic analysis plays important role in the identification of rock types through the observation of pore types, pore sizes and pore associations. Six rock types are identified, (1) PRT 1–vuggy porosity and moldic macropore association, (2) PRT 2–mudstone micropore and moldic macropore association, (3) PRT 3–intergrain meso-macropore association, (4) PRT 4–mudstone micropore and moldic mesopore association, (5) PRT 5– mudstone micropore and intergrain micro-mesopore association, and (6) PRT 6– mudstone micropore. Three-dimensional reservoir characterization through 3-D reservoir modeling is performed for facies, PRT and PRT-constrained porosity and permeability models. The modeling results show strong consistency between petrophysical properties and the underlying rock type models. High porosity and permeability values are mostly in association with reservoir quality rock types, those are PRT 1, PRT 2 and PRT 3. Reservoir quality evaluation reveals a strong relationship between the types, composition and spatial distribution of PRT and well’s productivity. PRT 1-dominated wells in majority exhibit high productivity (> 1,000 bfpd), PRT-2 dominated wells mostly show moderate productivity (500–1,000 bfpd), whereas the low productivity wells (< 500 bfpd) are commonly dominated by PRT 3.